"Just Birth": Childbirth Advocacy and the Rhetoric of Feminist Health Justice. Issue 2 (2nd April 2020) - West, Jennifer Ellis
Abstract: I examine writing produced in an online community of childbirth advocacy during a 2010 National Institutes of Health Conference convened to develop a consensus resolution on best practices regarding vaginal birth after cesarean (VBAC). Through an analysis of blog posts and comment threads written in response to the conference proceedings, I find that participants in the feminist counterpublic of birth advocacy utilize three primary strategies: they redefine VBAC as "just birth" rather than a medical "procedure;" they recontextualize the biomedical use of "risk" to include other factors outside of the immediate context of the hospital; and they reframe VBAC as a right rather than a preference. Together, these strategies work together to demonstrate the incommensurability of "shared doctor–patient decision making" within the current biomedical model of care. This move, toward a rights-based framework within a more highly contextualized systemic critique of health care, positions VBAC to be an issue that could link birth advocacy to a larger feminist health justice movement.